Women's empowerment and the intrinsic demand for agency: Experimental evidence from Nigeria - Bakhtiar, M. Mehrab; Fafchamps, Marcel; Goldstein, Markus; Leonard, Kenneth L.; Papineni, Sreelakshmi (National Bureau of Economic Research, 2022)
Most studies of intrahousehold resource allocation examine outcomes and do not consider the decision-making process by which those outcomes are achieved. We conduct an original lab-in-the-field experiment on the decision-making process of married couples over the allocation of rival and non-rival household goods. The experiment measures individual preferences over allocations and traces the process of consultation, communication, deferral, and accommodation by which couples implement these preferences. We find few differences in individual preferences over allocations of goods. However, wives and husbands have strong preferences over process: women prefer to defer budget allocation decisions to their husband even when deferral is costly and is not observed by the husband; the reverse is true for men. Our study follows a randomized controlled trial that ended a year earlier and gave large cash transfers over fifteen months to half of the women in the study. We estimate the effect of treatment on the demand for agency among women and find that the receipt of cash transfers does not change women's bargaining process except in a secret condition when the decision to defer is shrouded from her husband: only in that case does the cash transfer increase women's expressed demand for agency.